Salience of Language as an Ethnic Marker: A Snapshot of the Bidayuh of Sarawak, Malaysia - Ting, Su Hie; Campbell, Yvonne Michelle (2013)
Whether language is viewed as a necessity or an optional symbol of ethnic identity has profound influence on the retention of the language in the linguistic repertoire of future generations. The value attributed to language as an ethnic marker also has implications on whether language can function as an instrument of solidarity in the speech community. The study examined the salience of language as a marker of ethnicity for the indigenous Bidayuh community in Sarawak, Malaysia. The specific aspects studied were primary markers of ethnic identity and variations in perceptions across age groups. Questionnaires were distributed to 151 Bidayuhs from different age groups (secondary school students, university students, working adults). The participants ranked the importance of identity markers including parentage, language and other cultural elements. The results showed that Bidayuh parentage surfaced as an important ethnic marker only later in life but language is a salient ethnic symbol for all age groups. Another important ethnic symbol is the Gawai celebration, a harvest festival which has both religious and social significance. Interestingly the value placed on markers of ethnic membership increased with age, in spite of lessened use of Bidayuh in daily interactions. The findings are discussed in the context of ethnic identity categorisations.